Dinamika Hukum Kontrak di Era Ekonomi Digital dalam Perbandingan Kontrak Konvensional dan Smart Contract - Rizky Mahendra; Laila Puspitasari (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The emergence of smart contracts in digital transactions has transformed the traditional understanding of agreement, execution, and legal enforcement. In Indonesia, the absence of specific regulations concerning automated contracts raises questions regarding their validity, enforceability, and compliance with civil law principles. This study aims to examine the legal recognition and practical implementation of smart contracts using an empirical legal approach. Data were collected through semi-structured interviews with 12 legal practitioners, 8 business actors, and 5 digital system developers, complemented by document analysis and regulatory comparison. The findings indicate that 70 percent of respondents expressed uncertainty regarding the legal legitimacy of smart contracts, while 65 percent acknowledged their potential to enhance efficiency and transparency in business transactions. The research also reveals that regulatory gaps, limited institutional capacity, and technical errors such as coding bugs significantly affect the reliability of automated agreements. These results highlight that the adaptation of civil law principles, particularly consent and liability, remains incomplete in the context of digital automation. The study contributes to legal scholarship by proposing a reinterpretation of contract principles to align with technological innovation and emphasizing the need for hybrid regulatory frameworks. The novelty of this research lies in its empirical examination of how smart contracts challenge the classical notion of legal consent and create new dimensions of accountability within the modern digital legal system.